STRATEGI PEMASARAN TERHADAP PENJUALAN PRODUK TABUNGAN IB HASANAH DI PT. BANK NEGARA INDONESIA SYARIAH KANTOR CABANG JAKARTA BARAT - Raden Ajeng Entaresmen; Desy Putri Pertiwi (Jurnal Manajemen dan Pemasaran Jasa, 2016)
BNI Syariah branch office in West Jakarta has one of funding products that Savings iB Hasanah useful for pure investment vehicles Shariah compliance, where customers can make deposits and withdrawals of cash very easily. In marketing this product, BNI Syariah use 2 pattern to implement a marketing strategy that intensification patterns for customers who already have a product BNI Syariah and extension patterns for prospective customers at other banks that have not used that product at BNI Syariah. Besides, in general BNI Syariah has some marketing strategies that include 9P is Process, People, Product, Price, Place, Promotion, Partners, Presentation, and Passion. Employees who are experts in marketing their products to barriers such as the lack of make Savings iB Hasanah customers, how to services and lack of staff was quick to respond, competition between conventional banks and Islamic banks BNI Syariah office supplies in some areas.Keywords : Marketing strategy, Savings iB Hasanah, Product marketing barriers savings iB Hasanah